Integrated computer network systems - Welsh, Frank 1957- (Computer-aided engineering (New York, N.Y.), 1992)
This single-source reference offers complete coverage of computer network design, implementation, management, and functionality. Discussing all major areas related to computer networks, "Integrated Computer Network Systems" describes: techniques for interoperability testing; network design considerations before implementation; the relationship between user and vendor; product selection and manufacturing; and network management, including network behaviour, problem solving, and future growth. With a full glossary of terms and over 50 diagrams, "Integrated Computer Network Systems" is a resource for manufacturing, industrial, and systems engineers; network managers and technicians; computer systems consultants; and upper-level undergraduate and graduate students in computer science and computer network courses.